2021
DOI: 10.3389/fmars.2021.771630
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Marine Aquaponics: Effects of Shrimp to Plant Ratios and C/N Ratios

Abstract: Integrated aquaponic food production systems are capable of producing more food on less land using less water than conventional food systems, and marine systems offer the potential of conserving freshwater resources. However, there have been few evaluations of species combinations or operational parameters in marine aquaponics. The goal of this experiment was evaluation of stocking density ratio of Pacific whiteleg shrimp (Litopenaeus vannamei) to three edible halophytes (Atriplex hortensis, Salsola komarovii,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 52 publications
1
9
1
Order By: Relevance
“…In the interim between experiments, evaporative losses were replaced with well water, constant aeration was provided to all subsystems and probiotics (EZ-Bio, Bacillus spp., Zeigler Brothers, Gardners, PA, United States) were added weekly at a dose of 10 ppm EZ-bio once a week. Once shrimp moved into experimental units, additional doses of probiotics were added every other day in the 1st week, twice per week in the 2nd week, and once per week beginning in the 3rd week continuing until the end of the experiment (Crab et al, 2010;Chu, 2014;Chu and Brown, 2021b). Molasses (Hawthorne Gardening Co., Vancouver, WA, United States) was provided as an organic carbon source for the adjustment of C/N ratio.…”
Section: Experimental Design and System Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…In the interim between experiments, evaporative losses were replaced with well water, constant aeration was provided to all subsystems and probiotics (EZ-Bio, Bacillus spp., Zeigler Brothers, Gardners, PA, United States) were added weekly at a dose of 10 ppm EZ-bio once a week. Once shrimp moved into experimental units, additional doses of probiotics were added every other day in the 1st week, twice per week in the 2nd week, and once per week beginning in the 3rd week continuing until the end of the experiment (Crab et al, 2010;Chu, 2014;Chu and Brown, 2021b). Molasses (Hawthorne Gardening Co., Vancouver, WA, United States) was provided as an organic carbon source for the adjustment of C/N ratio.…”
Section: Experimental Design and System Managementmentioning
confidence: 99%
“…This result aligned with the findings reported by other researchers (Otoshi et al, 2011;Cerozi and Fitzsimmons, 2016;Chu and Brown, 2021a,b). TAN can be stabilized and remain below 0.1 mg/L within 3 weeks in new systems via inoculating probiotics on a regular basis (Cerozi and Fitzsimmons, 2016;Chu and Brown, 2021b). demonstrated that the concentrations of TAN and NO 2 − remained under 0.51ppm and 1.25 mg/L, respectively, by introducing biofloc from an established system prior to the experiment.…”
Section: Water Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrient flows in aquaponics varies as a function of feeding frequency and regime, feed amounts, animal to plant ratio, hydraulic loading rate, subsystem ratio, and pH [9][10][11][12][13][14][15][16]. Environmental pH plays a critical role in nearly all chemical reactions in water, and influences physiological functioning of aquatic animals, plants, and microorganisms [4,13,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…the probability of a pH conundrum in marine or brackish water aquaponic systems may be less than in freshwater systems. Nevertheless, Chu and Brown [9,21] mentioned that pH was a possible factor influencing growth of the halophytes they evaluated. The ideal range of pH for an integrated system that includes aquatic animals, plants and bacteria in marine aquaponics remains largely unknown and may significantly influence compatibility of biotic subsystems and significantly influence outputs.…”
Section: Introductionmentioning
confidence: 99%